An extended challenge-based framework for pracitce design in sports coaching - Hodges, N. J.; Lohse, K. R. (Journal of Sports Sciences, 2022)
The challenge-point framework as a model for thinking about motor learning was first proposed in 2004. Although it has been well-cited, surprisingly this framework has not made its way into much of the applied sport science literature. One of the reasons for this omission is that the original framework had not been encapsulated into a paper accessible for sports practitioners. The framework had mostly a theoretical focus, providing a mechanistic summary of motor learning research. Our aims in this paper were to explain and elaborate on the challenge point framework to present an applied framework guiding practice design. We connect the framework to other theories that involve predictive coding, where information is attended when it disconfirms current predictions, providing a strong signal for learning. We also consider how two new dimensions (learners` motivation and practice specificity) need to be considered when designing practice settings. By moving around the different dimensions of functional difficulty, motivation, and specificity, coaches can optimize practice to achieve different learning goals. Specifically, we present three general "types" of practice: practice to learn, to transfer to competition, and to maintain current skills. Practical examples are given to illustrate how this framework can inform coach practice.